2011
DOI: 10.3152/030234211x12960315267895
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and individual determinants of patent production of academic scientists and engineers in the United States

Abstract: This article contributes to an important literature on the determinants of academic patenting. We develop and test a model that predicts how individual characteristics and organizational factors affect individual patenting production. The analysis uses zero-inflated negative binomial regression on data from a 2010 national survey of 1,379 US-based university scientists and engineers, 624 of which hold no patents assigned to their current university. Findings from this research generally support our hypotheses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Ó 2016 The Economic Society of Australia as the strategy and resources of the laboratory. This is consistent with other research that finds that individual preferences and characteristics are an important predictor of the number of patent applications that faculty produce (Huang et al, 2011). Notes: Standard errors in parentheses, ***P < 0.01, **P < 0.05, *P < 0.1.…”
Section: Estimation Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Ó 2016 The Economic Society of Australia as the strategy and resources of the laboratory. This is consistent with other research that finds that individual preferences and characteristics are an important predictor of the number of patent applications that faculty produce (Huang et al, 2011). Notes: Standard errors in parentheses, ***P < 0.01, **P < 0.05, *P < 0.1.…”
Section: Estimation Resultssupporting
confidence: 88%
“…These individual effects assume all other things are held constant, such as the strategy and resources of the laboratory. This is consistent with other research that finds that individual preferences and characteristics are an important predictor of the number of patent applications that faculty produce (Huang et al ., ).…”
Section: Estimation Resultsmentioning
confidence: 97%
“…In the case of RI universities, one might describe cultural cognitive public value institutions as efforts to increase service to undergraduates, commitments to diversity, and beliefs that the organization’s values can shape public outcomes. For example, faculty perceptions of shifting university priorities toward commercialization and department incentives to patent may affect faculty commitments to traditional university activities such as publishing and teaching and shift faculty outcomes (Bozeman 2000; Huang, Feeney, Welch 2011). Faculty also may respond to private market demands and university commitments to increase university–industry partnerships, at the expense of the production of public goods (Slaughter and Leslie 1997).…”
mentioning
confidence: 99%
“…First, several studies are pointing to institutional factors that encourage patenting. For example, Huan and colleagues () utilized a national survey of university scientists and engineers and found that both individual and organizational factors were correlated with individual patent production. Primarily, they found that universities that provided departments financial incentives were associated with higher quantities of patenting.…”
Section: Patentsmentioning
confidence: 99%